Frequency of Helicobacter Pylori Infection in Patients with Functional Dyspepsia - Wajeeha Rafi, Ammar Noor, Hafiz Muhammad Hashim Khan, Tayyab Arif Butt, Muhammad Inam Ul Haq, Muhammad Mohsin Bajwa (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of Helicobacter Pylori (H. Pylori) infection in patients of dyspepsia. Patients and Methods: A total number of 150 patients with diagnosis of dyspepsia, both male and female having age 18-60 years and having duration of symptoms of dyspepsia from > 6 months were included from June-2021 to February-2022. Baseline characteristics such as age, gender, duration of symptoms, educational status and marital status was noted. In laboratory gram staining and rapid urease test was done to diagnose H. pylori. Diagnostic endoscopy was done in all patients. Biopsy specimens was taken from abnormal lesions for histopathological diagnosis of H. pylori infection. Results: Mean age was 40.11±9.08 years. Mean duration of symptoms was 13.24±5.42 months. There were 72(48%) male patients and 78(52%) female patients. Helicobacter pylori was found present in 86 (50.89%) and it was absent in 83 (49.11%) patients Conclusion: In present study, H. Pylori was diagnosed in 50.89% patients which is very high, so the patients presenting with functional dyspepsia should always be evaluated first for the possibility of H. Pylori infection.